Nickel release and the microstructure of stainless steel orthodontic archwire surfaces after immersion in detergent and non-detergent toothpaste: an in vitro study - Hilda Fitria Lubis; Kholidina Imanda Harahap; Dina Hudiya Nadana Lubis (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Stainless steel is a material that can be used in orthodontics for components of dental braces, such as brackets, archwires and molar bands. Orthodontic archwires exposed to toothpaste can release nickel ions that cause hypersensitivity. The excessive use of sodium lauryl sulphate in detergent toothpaste can cause mouth irritation, severe ulceration, decreased salivary solubility and taste sensitivity changes. Purpose: The aim of this study is to compare the nickel ion released by stainless steel archwires after immersion in detergent and non-detergent toothpaste. Methods: Forty stainless steel archwires from Ortho Organizer (0.016 x 0.022in) were divided into two groups (n=20). Group 1 comprised stainless steel archwires immersed in detergent toothpaste. Group 2 consisted of stainless steel archwires immersed in non-detergent toothpaste. These archwires were immersed in 1.5g toothpaste then kept in an incubator at 37°C for around 24 hours. After that, the archwires were removed from the toothpaste, and the toothpaste was dissolved in 25ml of Aquadest. The amount of nickel ion released was examined by using inductively coupled plasma optical emission spectrometry (ICP-OES). After that, the structure of the sample surface was examined with a scanning electron microscope (SEM). A statistical analysis was done using the Shapiro–Wilk normality test (p>0.05). An independent t-test was carried out to compare the two groups (p<0.05). Results: The mean of nickel ion release in group 1 was 0.214±0.319mg/l, and in group 2 it was 0.168±0.107 mg/l. There was no significance between the groups (p=0.323; p>0.05). The SEM images of the archwire surfaces showed that there were more corrosive contour changes in the archwire surface in group 1 than in group 2. Conclusion: There was no difference between the nickel ion released from stainless steel orthodontic archwires after immersion in detergent and non-detergent toothpaste. After immersion in detergent toothpaste, stainless steel archwire surfaces showed more corrosive contour changes than those immersed in non-detergent toothpaste.